Strategi Coping pada Santri Penghafal Al-Qur’an 30 Juz di Kudus - Sodiq, Alwi Mahardhika; Widjanarko, Mochamad; Suharsono, Suharsono (Universitas Al Azhar Indonesia, 2023)
Memorizing the Quran is an effort that demands sincerity and struggle. In the process, Quranic memorization students (santri) often experience stress. Stress can be caused by various factors, such as the high memorization demands, strict rules in the Islamic boarding school (pondok pesantren), and being far from their families. To overcome stress, Quranic memorization students can use coping strategies. The purpose of this research is to analyze the sources of stress and describe coping strategies among Quranic memorization students who experience boredom and pressure in the Islamic boarding school. The research method used in this study is qualitative, with data collection techniques through observation, interviews, and documentation. Data analysis involves data collection, data reduction, data presentation, and drawing conclusions. The research location is in the Islamic boarding school area of Kota Kudus. There are four subjects involved in this research, including two males and two females. The results of this study indicate that sources of human stress come from three sources: from within the individual, from the family, and from the environment. The coping strategies used by the subjects involve controlling what can happen between the individual and the environment through problem-solving, decision-making, and direct actions.Keywords - Coping Strategy, Islamic Boarding School, Santri, Memorization